Preparation to care for confused older patients in general hospitals: a study of UK health professionals - Griffiths, Amanda; Knight, Alec; Harwood, Rowan H.; Gladman, John R.F. (Oxford University Press, 2013)
Background and Objective: in the UK, two-thirds of patients in general hospitals are older than 70, of whom half have dementia or delirium or both. Our objective was to explore doctors, nurses and allied health professionals' perceptions of their preparation to care for confused older patients on general hospital wards.